Analisis Prarancangan Suatu Industri Kimia - Eva Fadillah (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
The chemical industry is a vital sector in the global economy that requires careful and planned approaches in designing production facilities. This article discusses the pre-design analysis of a chemical industry focusing on process identification, technology selection, production capacity calculation, capital cost estimation, and environmental impact evaluation. The analysis methods involve the latest techniques in chemical engineering and economic evaluation. The results provide deep insights into the key factors influencing the success of the proposed chemical industry. Emphasis on sustainability and environmental performance is also crucial in the pre-design of modern chemical industries. The conclusion of this study offers a clear perspective on critical aspects to consider in designing an efficient, sustainable, and competitive chemical industry in the increasingly complex industrial era.